VD_FINDINFO HC / 2021 / 638 vom 24. August 2021 - VD Tribunal cantonal (2021)
LIBÉRATION JUDICIAIRE D'UNE SERVITUDE, INTERDICTION DES IMMISSIONS EXCESSIVES, ACTION EN CESSATION DE TROUBLE | 684 CC, 736 al. 2 CC